2020
DOI: 10.1177/1468087420963986
|View full text |Cite
|
Sign up to set email alerts
|

Hole-to-hole variations in coupled flow and spray simulation of a double-layer multi-holes diesel nozzle

Abstract: In diesel engines, double-layer multi-holes nozzles contribute significantly in making spray injection uniform in both the circumferential and axial directions; they further ensure that minimal or no interactions are encountered among the spray jets emerging from the nozzle holes and positively affect fuel atomisation and enhance mixing during engine operation. In this study, the variation in internal flow characteristics and spray patterns from the upper and the lower layer nozzle holes were investigated expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The comparison of prediction results showed good agreements with the experimental results for mean velocity but underpredicted the RMS velocity where cell size was not very fine. The variation in internal flow characteristics and spray patterns in diesel engine from the upper and the lower layer nozzle holes have been investigated recently by Wang et al 23 experimentally (using X-ray scans) and computationally (using Eulerian-Eulerian two-phase flow and Lagrangian spray models); the results showed that the cavitation development within the upper layer holes is more intense than those formed within the lower layer nozzle holes leading to higher injection rates from the lower layer nozzle holes and that they also exhibit less cycle-to-cycle variations in the observed spray patterns. Also, Mohan et al 24 simulated in-nozzle flow and spray (flashing and non-flashing) in IC engine using a coupled Eulerian-Lagrangian approach and Lagrangian spray models, and the results showed good quantitative agreements between the liquid and vapor penetration lengths with the published experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of prediction results showed good agreements with the experimental results for mean velocity but underpredicted the RMS velocity where cell size was not very fine. The variation in internal flow characteristics and spray patterns in diesel engine from the upper and the lower layer nozzle holes have been investigated recently by Wang et al 23 experimentally (using X-ray scans) and computationally (using Eulerian-Eulerian two-phase flow and Lagrangian spray models); the results showed that the cavitation development within the upper layer holes is more intense than those formed within the lower layer nozzle holes leading to higher injection rates from the lower layer nozzle holes and that they also exhibit less cycle-to-cycle variations in the observed spray patterns. Also, Mohan et al 24 simulated in-nozzle flow and spray (flashing and non-flashing) in IC engine using a coupled Eulerian-Lagrangian approach and Lagrangian spray models, and the results showed good quantitative agreements between the liquid and vapor penetration lengths with the published experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature in the combustion chamber varied from 700 K to 1500 K. The pressure in the combustion chamber was 100 bar for octane and 80 bar for dodecane and the injection velocity was 350 m/s in both cases. These values were taken from previous works of the authors [19][20][21][22][23]. distribution of liquid fuel droplets (octane and dodecane), respectively.…”
Section: Mathematical and Physical Statement Of The Problemmentioning
confidence: 99%
“…Fuel economy and emission cleanliness have gradually become the primary factors to be considered in diesel engine with proposing the concept of “energy saving” and “environmental protection.” 1,2 The electronic high-pressure common rail fuel injection system is equivalent to the “heart” and “brain” of the internal combustion engine, and is regarded as a landmark technology to improve fuel economy and reduce pollutant emissions. 3,4 Injector nozzle is the most critical core component in high-pressure common-rail fuel injection system, 57 which is related to the accuracy and stability of fuel injection system. Cavitation phenomenon performs the most common two-phase flow in the nozzle with high turbulence and strong compression.…”
Section: Introductionmentioning
confidence: 99%